Analysis of Science Process Skills Based on Programme for International Student Assessment Test and Observation Instruments of Senior High Schools - Agustiani, E; Aminah, N. S.; Suryana, R. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2022)
This research aims to figure out the students' Science Process Skills (SPS) using problem tests of Programme for International Assessment (PISA) and observation instruments in Senior High School at Bojonegoro Regency. This work is descriptive research. As research subjects, 100 students in the eleventh grade were chosen randomly from three schools in 2019/2020. The Pisa test consists of 6 questions that have aspects of SPS: measuring, applying concepts, inferring, and predicting. The problem tests of PISA resulted that 36% of students attained scores above 60. Furthermore, students’ percentage could complete the measuring aspects, predicting aspects, applying concepts, and the inferring aspects were 64%, 38%, 36%, and 42%. Students’ percentage based on observation instruments' results were predicting 52%, applying concepts 43%, measuring 48%, inferring 46%, experimenting 0%, asking question 23%, classifying 37%, communicating 28%, and observing 55%. These are beneficial for teachers to improve the learning process according to student needs.